2017
DOI: 10.1016/j.ejogrb.2017.01.058
|View full text |Cite
|
Sign up to set email alerts
|

Operative and diagnostic hysteroscopy: A novel learning model combining new animal models and virtual reality simulation

Abstract: GPAs were significantly higher after the workshop was completed. The biggest difference was observed in operative knowledge (0,28 GPA before workshop versus 0,55 after workshop, p<0,05). All of the 25 residents having completed the workshop applauded the realism an efficiency of this type of training. The force feedback allowed by the cattle uteruses gives the residents the possibility to manage thickness of resection as in real time surgery. Furthermore, the two-horned bovine uteruses allowed to reproduce sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Bassil et al (2017) [ 35 ] reported a novel learning method that combined VR simulation and animal models for training in operative and diagnostic hysteroscopy. In this study, end-year obstetrics and gynecology residents performed different surgical skills on VR simulators as well as animal specimens (bovine uterus and bladder) after receiving a full-day workshop.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Bassil et al (2017) [ 35 ] reported a novel learning method that combined VR simulation and animal models for training in operative and diagnostic hysteroscopy. In this study, end-year obstetrics and gynecology residents performed different surgical skills on VR simulators as well as animal specimens (bovine uterus and bladder) after receiving a full-day workshop.…”
Section: Resultsmentioning
confidence: 99%
“…Of the articles we included in our review, 11 and 13 studies were based on VR and AR, respectively. Among the VR studies, one of them was based on non-immersive VR and was performed using a monitor or a screen [ 52 ], four articles were based on semi-immersive VR [ 34 , 35 , 36 , 37 ], and six of them were based on full-immersive VR [ 3 , 12 , 39 , 46 , 47 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The percentage of gynecologists who still perform diagnostic hysteroscopy in a questionable way, who are not familiar with the endoscopic view, and who use incorrect methods to gain access to the uterine cavity may still be high. Therefore, there is a need for training programs that aim to provide theoretical concepts and practical principles to perform the correct technique and to provide adequate training to gynecologists [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the last decade, several models have been proposed for training in hysteroscopy. In order to reproduce the anatomy of the uterus and the characteristics of its tissues as accurately as possible, simulators based on vegetables and animal models, as well as synthetic and virtual models, have been designed and described [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%